PCR-RFLP for Detection of Fusarium graminearum Genotypes with Resistance to Phenamacril - Li, Jiao-Sheng (Plant disease, 2021)
Phenamacril is a cyanoacrylate fungicide that provides excellent control of Fusarium head blight (FHB) or wheat scab, which is caused predominantly by Fusarium graminearum and F. asiaticum. Previous studies revealed that codon mutations of the myosin-5 gene of Fusarium spp. conferred resistance to phenamacril in in vitro lab experiments. In this study, PCR restriction fragment length polymorphism (RFLP) was developed to detect three common mutations (A135T, GCC to ACC at codon 135; S217L, TCA to TTA at codon 217; and E420K, GAA to AAA at codon 420) in F. graminearum induced by fungicide domestication in vitro. PCR products of 841 bp (for mutation of A135T), 802 bp (for mutation of S217L), or 1,649 bp (for mutation of E420K) in the myosin-5 gene were amplified by appropriate primer pairs. Restriction enzyme KpnI, TasI, or DraI was used to distinguish phenamacril-sensitive and -resistant strains with mutation genotypes of A135T, S217L, and E420K, respectively. KpnI digested the 841-bp PCR products of phenamacril-resistant strains with codon mutation A135T into two fragments of 256 and 585 bp. In contrast, KpnI did not digest the PCR products of sensitive strains. TasI digested the 802-bp PCR products of phenamacril-resistant strains with codon mutation S217L into three fragments of 461, 287, and 54 bp. In contrast, TasI digestion of the 802-bp PCR products of phenamacril-sensitive strains resulted in only two fragments of 515 and 287 bp. DraI digested the 1,649-bp PCR products of phenamacril-resistant strains with codon mutation E420K into two fragments of 932 and 717 bp, while the PCR products of phenamacril-sensitive strains was not digested. The three genotypes of resistance mutations were determined by analyzing electrophoresis patterns of the digestion fragments of PCR products. The PCR-RFLP method was evaluated on 48 phenamacril-resistant strains induced by fungicide domestication in vitro and compared with the conventional method (mycelial growth on fungicide-amended agar). The accuracy of the PCR-RFLP method for detecting the three mutation genotypes of F. graminearum resistant to phenamacril was 95.12% compared with conventional method. Bioinformatics analysis revealed that the PCR-RFLP method could also be used to detect the codon mutations of A135T and E420K in F. asiaticum